Pengaturan Tegangan PLTMH 5000 WATT Menggunakan Trafo Dengan Tap Yang Terkontrol Mikrokontroler ATmega 8535 - Prasetio, Novan Giri (Jurnal Informatika dan Teknik Elektro Terapan (JITET), 2013)
AbstractTalang Java Village in Sukau district, West Lampung, is a villages that have no access to electricity of PT. PLN (Persero).  To meet the demand for electricity, people used the MHP(micro hydro power plants) as a source of electrical energy. MHP in talang Java village have several problems, which one is the distance of a potential energy source to residential areas which resulted distance the center of the load to generator It is cause voltage unstable system so that the voltage at the load side at low level. To overcome problem of unstable voltage, designed a tool in the form of a transformer which can regulate the voltage on the load side to a safe level. Moreover  the transformer equipped with a control circuit based AT Mega 8535 microcontroller. The use of a controller circuit aims to control voltage changes in MHP. From the test results, found that the load side voltage after mounted transformer, an increase. At first the voltage on the load side at the level of 150 volt, then  after the installation of transformers, voltage level is at 180 volt-220 volt.Keyword: Transformer, Voltage, Microcontroller